Analisis Pertimbangan Hakim dalam Membedakan Gugatan Wanprestasi dan Perbuatan Melawan Hukum untuk Mewujudkan Kepastian Hukum Perdata - Mesya Assauma Nurfitrah; Poppy Felicia Butarbutar; Msy. Hamda Rifa Al Zulaikha; Dian Aprilia (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Legal certainty in civil disputes depends heavily on the accuracy of determining the legal basis of a claim. In practice, however, the conflation of breach of contract (wanprestasi) and unlawful act (onrechtmatige daad) claims remains a recurring problem in Indonesian civil courts. Despite sharing surface similarities, these two causes of action are fundamentally distinct in terms of their legal concept, statutory basis, and juridical consequences. Misclassification of either claim directly affects the burden of proof, the construction of the petitum, the form of compensation sought, and the legal standing of the parties involved. This article seeks to analyze how judges differentiate between these two types of claims based on court decisions, while also mapping the patterns of judicial reasoning and their implications in achieving legal certainty in civil law. This article employs a normative juridical method with a descriptive-analytical approach, examining relevant provisions of the Indonesian Civil Code (Burgerlijk Wetboek) and pertinent jurisprudence as the primary legal materials. The findings of this study are expected to contribute to the development of civil procedural law in Indonesia and serve as a reference for legal practitioners in accurately constructing civil claims, thereby avoiding misclassification that may prejudice their clients' legal interests in court proceedings.